Mitochondrial haplogroup H1 is protective for ischemic stroke in Portuguese patient - Rosa, A (2012)
BACKGROUND: The genetic contribution to stroke is well established but it has proven difficult to identify the genes and the disease-associated alleles mediating this effect, possibly because only nuclear genes have been intensely investigated so far. Mitochondrial DNA (mtDNA) has been implicated in several disorders having stroke as one of its clinical manifestations. The aim of this case-control study was to assess the contribution of mtDNA polymorphisms and haplogroups to ischemic stroke risk. METHODS: We genotyped 19 mtDNA single nucleotide polymorphisms (SNPs) defining the major European haplogroups in 534 ischemic stroke patients and 499 controls collected in Portugal, and tested their allelic and haplogroup association with ischemic stroke risk. RESULTS: Haplogroup H1 was found to be significantly less frequent in stroke patients than in controls (OR = 0.61, 95% CI = 0.45-0.83, p = 0.001), when comparing each clade against all other haplogroups pooled together. Conversely, the pre-HV/HV and U mtDNA lineages emerge as potential genetic factors conferring risk for stroke (OR = 3.14, 95% CI = 1.41-7.01, p = 0.003, and OR = 2.87, 95% CI = 1.13-7.28, p = 0.021, respectively). SNPs m.3010G>A, m.7028C>T and m.11719G>A strongly influence ischemic stroke risk, their allelic state in haplogroup H1 corroborating its protective effect. CONCLUSION: Our data suggests that mitochondrial haplogroup H1 has an impact on ischemic stroke risk in a Portuguese sample.